Practice and exploration on Shenzhen"Kintsmesh Project" based on integrality data - Dongping CHEN (大数据)
Some important issues need to be addressed to facilitate the gravity shift in governance from authority to the people, from government to society and from power to rights to establish the service-style government as the central committee of the CPC requires. These are important topics for research in the top-level design for building smart e-government in the background of big data. Combining with the requirements of the construction of the service-type government, the problems existing in the traditional electronic government were analyzed, and the ideas of smart government affairs designs and implementation paths were supported, basing on the concept of overall data driven. A system of smart government which has the government logic and data model as its core was attempted to design.